ОРОЛБЎЙИ ЛАНДШАФТЛАРИДА ЭКОЛОГИК БАРҚАРОРЛИКНИ ТАЪМИНЛАШ МАСАЛАЛАРИ - Назаров, Х.Т.; Ибрагимов, Л.З.; Қушоқова, Ф.; Бобоев, С. (SCIENCE and SOCIETY, 2021)
The article deals with social problems which caused the to ecological problems because of drying up Aral Sea at the end 60s, al though some solections are presented here. There are given suggestions, recommendations and methodological recommendations on stabilizing ecological conditions of Aral basin, these mentioned suggestious night be accomplished in the oplimized conditions of the ecological essense of territory.
Keywords: degradation; continental climate; saline aerosol; ecosystem in delta; coastal ditches; microclimates; forest landscapes